An investigation of the link between the bacterial derived queuine molecule and tyrosine production - Rakovich, Tatsiana (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2011)
Queuine, a dietary derived 7-deazaguanine molecule, has previously been shown to prevent lethality and other symptoms in germ-free mice that were maintained on a tyrosine-free diet. This work suggested a link between queuine and tyrosine biosynthesis or tyrosine utilisation in higher eukaryotes.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.